Cytoplasmic Expression of the ALS/FTD-Related Protein TDP-43 Decreases Global Translation Both in vitro and in vivo - Charif, Santiago E.; Luchelli, Luciana; Vila, Antonella; Blaustein, Matías; Igaz, Lionel M. (Frontiers in Cellular Neuroscience, 2020)
TDP-43 is a major component of cytoplasmic inclusions observed in neurodegenerative diseases like frontotemporal dementia (FTD) and amyotrophic lateral sclerosis (ALS). To further understand the role of TDP-43 in mRNA/protein metabolism and proteostasis, we used a combined approach with cellular and animal models overexpressing a cytoplasmic form of human TDP-43 (TDP-43-ΔNLS), recapitulating ALS/FTD features. We applied in HEK293 cells a method for labeling de novo translation, surface sensing of translation (SUnSET), based on puromycin (PURO) incorporation. While control cells displayed robust puromycilation, TDP-43-NLS transfected cells exhibited reduced ongoing protein synthesis. Next, by using a transgenic mouse overexpressing cytoplasmic TDP-43 in the forebrain (TDP-43-ΔNLS mice) we assessed whether cytoplasmic TDP-43 regulates global translation in vivo. Polysome profiling of brain cortices from transgenic mice showed a shift towards non-polysomal fractions as compared to wild-type littermates, indicating a decrease in global translation. Lastly, cellular level translational assessment by SUNSET was performed in TDP-43-ΔNLS mice brain slices. Control mice slices incubated with PURO exhibited robust cytoplasmic PURO signal in layer 5 neurons from motor cortex, and normal nuclear TDP-43 staining. Neurons in TDP-43-NLS mice slices incubated with PURO exhibited high cytoplasmic expression of TDP-43 and reduced puromycilation respect to control mice. These in vitro and in vivo results indicate that cytoplasmic TDP-43 decreases global translation and potentially cause functional/cytotoxic effects as observed in ALS/FTD. Our study provide in vivo evidence (by two independent and complementary methods) for a role of mislocalized TDP-43 in the regulation of global mRNA translation, with implications for TDP-43 proteinopathies.